Technical Barriers to Trade Agreement, the Sanitary and Phytosanitary Measures Agreement, and the General Agreement on Tariffs and Trade : a map of the World Trade Organization Law of Domestic Regulation of Goods - Marceau, Gabrielle (2002)
Compares the disciplines on domestic regulation contained in each of the agreements. Provides an analysis of the conditions for application of each agreement and the possibility for overlap and conflict among these agreements.